Impact of Corona Virus Disease-19 Pandemic on Co-Assistant Mental Health - Mayang Sari Ayu; Mayasari Ramadhani (Faculty of Medicine, Public Health, and Nursing, 2022)
Background: The Coronavirus Disease 2019 (COVID-19) pandemic has an impact on the physical and mental health of individuals and all of society. During the COVID pandemic, all social and physical activities of each individual are limited. Physical-social distancing or physical restrictions have an impact on mental health and psychological problems. This anxiety is also experienced by medical students as Co-Assistants (young doctors) during their education in hospitals. Objectives: This study aimed to discuss matters related to the impact of the COVID-19 on medical students’ mental health during the pandemic. Method: This cross-sectional study used the Self-Reporting Questionnaire-20. Mental health problems of college students during the pandemic were assessed and analyzed for their level of anxiety. This study involved 69 medical students as Co-Assistants (young doctors) in the professional study program using purposive sampling technique. Results: The results of the study found that among Co-Assistants who underwent clinical clerkship during the COVID-19 pandemic as much as 44.9% experienced mental health disorders. We also found that the female Co-Assistants were twice as likely to experience mental health problems as male Co-Assistants. The most common type of mental health problem was experiencing symptoms of depression. Conclusion: During the two years of the pandemic, while living the ‘new normal’, Co-Assistants felt the fear of being infected with the lack of personal protective equipment, economic problems for their parents, and facing the challenges of distance education. In comparing the mental health problems of the Co-Assistants, the most common during the COVID-19 pandemic were the symptoms of depression.